ENTREPRENEURSHIP AS A DIRECTION OF IMPLEMENTATION OF CAREER PLANS OF STUDENTS OF VOCATIONAL (VOCATIONAL AND TECHNICAL) EDUCATIONAL INSTITUTIONS (Innovative professional education, 2022)
The further development of the state directly depends on the readiness and ability of young people to engage in entrepreneurial activity. A study of the career plans of students of professional (vocational) education institutions for the near future (up to five years) allows us to conclude that they are primarily related to the chosen field of vocational training, and, secondly, in largely focused on business. The results of the study revealed several trends. First of all, there is a decrease in the number of students who plan to engage in entrepreneurial activities in the future.
Keywords: vocational education; preparation for entrepreneurship; youth entrepreneurship; career plans; career counseling